Malaysian Civil Society Organizations (CSOs) perspective on child marriage - Mohd Al Adib Samuri,; Nurhafilah Musa,; Helmiah Abd Razak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In Malaysia, Civil Society Organizations (CSOs) play a pivotal role in advocating against child marriage and influencing societal perceptions of this detrimental practice. While the Malaysian government has made efforts to address this issue, the proposal to legally raise the marriageable age to 18 for all genders has been met with mixed reactions from different segments of society. This study aims to investigate the viewpoints of Malaysian CSOs on child marriage. A roundtable discussion was held with 11 representatives from organisations focusing on children’s and women’s issues. The findings reveal a consensus among most participants against child marriage, citing children’s rights violations and misconceptions about children’s maturity and the nature of marriage. Contrarily, some Muslim factions endorse child marriage for religious reasons, leading to varied opinions among CSO members, ranging from outright opposition to conditional or complete acceptance. The study highlights key reasons for opposing child marriage, such as the infringement of children’s rights, concerns about sexual and reproductive health, and the vulnerability of children. It also outlines CSO strategies for combating child marriage, including reshaping public discourse, emphasising girls’ education, and providing targeted sexual and reproductive health education to at-risk youth.